Serum sPECAM-1 and sVCAM-1 levels are associated with conversion to multiple sclerosis in patients with optic neuritis - Kalinowska-Łyszczarz, Alicja; Michalak, Sławomir; Pawlak, Mikołaj A.; Losy, Jacek; Kozubski, Wojciech (Journal of neuroimmunology, 2016)
Platelet-Endothelial-Cell-Adhesion-Molecule-1 (PECAM-1) and Human-Vascular-CAM-1 (VCAM-1) are adhesion molecules involved in leukocyte-endothelial interaction. In our study serum levels of sPECAM-1 and sVCAM-1 were measured (ELISA) in twenty-nine patients during their first monosymptomatic optic neuritis (ON) episode. Anti-aquaporin-4-antibodies (AQP4-IgG) were detected with the cell-based assay. Patients were followed for seven years, during which 16/24 AQP4-IgG (−) patients developed MS and 2/5 AQP4-IgG (+) patients developed NMO. Patients who developed MS had significantly lower sPECAM-1 and sVCAM-1 than those who did not. Serum sPECAM-1 and sVCAM-1 may turn out to be useful biomarkers correlated with the risk of progression to MS after first ON incident. •Serum levels of PECAM-1 and VCAM-1 could correlate with the risk of progression to MS after first optic neuritis incident.•sPECAM-1 and sVCAM-1 levels during first optic neuritis are lower in subjects progressing to MS in a 7-year follow-up.•In our cohort only 2 out of 5 AQP4-IgG (+) optic neuritis patients developed clinically definite NMO in a 7-year follow-up.•Although AQP4-IgGs are considered highly NMO-specific, it remains uncertain if they may appear in other autoimmune diseases.